HUBUNGAN PROFESIONALISME GURU FIQH TERHADAP HASIL BELAJAR SISWA KELAS X DI MADRASAH ALIYAH NEGERI KOTA BATU - Muhammad Ilham Abiyasa; Anwar Sa’dullah; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This studi aims to prove that there is a significant relationship to the Professionalism of Fiqh Teachers with the Learning Outcomes of class X students at Madrasah Aliyah Negeri Batu. While the sample in this study was 10% of students in class x totaling 30 students. The techniques used in data collection are observation, questionnaires and documentation. Researchers used data analysis techniques in the form of validity test analysis and Reliability, Normality and Linearity tests, also product moment statistics and simple linear regression. This type of research is an ex-post facto correlation study. Based on the results of research and discussion obtained, it can be taken the conclusion that there is a significant relationship between the professionalism of fiqh teachers with the learning outcomes of students of class X Madrasah Aliyah Negeri Batu. This is evidenced by the correlation value of the X variable with the Y variable has a count value of 0.814 which is at the coefficient interval value of 0.800 - 0.1 then it can be said that the level of relationship between variables X and Y is strong